THE EFFECTIVIVITY OF MATHEMATICS COOPERATIVE LEARNING MODELS THINK PAIR SHARE (TPS) AND STUDENT TEAMS-ACHIEVEMENT DIVISIONS (STAD) COMBINED WITH SCIENTIFIC APPROACH IN TERM OF MATHEMATICAL COMMUNICATION SKILL OF STUDENTS GRADE 8 TH SMP N 1 SLEMAN - Ghosa Kurnia Fistika; Sugiyono Sugiyono (Universitas Negeri Yogyakarta, 2016)
AbstractThe aim of this study was to determine: (1) the effectiveness of cooperative learning model Think Pair Share (TPS) with Scientific approach in terms of mathematical communication skills of learners; (2) the effectiveness of cooperative learning model Student Teams-Achievement Divisions (STAD) with Scientific approach in terms of mathematical communication skills of learners; and (3) which is more effective among cooperative learning model Think Pair Share (TPS) with Scientific approach and cooperative learning Student Teams Achievement Divisions (STAD) with Scientific approach to mathematical communication skills of learners. This is a quasi-experimental study, using two experimental groups. Instruments to measure the ability of mathematical communications in the form of shaped test item description. Based on hypothesis testing using a significance level of 5% can be concluded that: (1) cooperative learning model type TPS with scientific approach was effective in terms of communication skills of mathematics, (2) cooperative learning model type STAD scientific approach was effective in terms of communication skills mathematical , (3) cooperative learning model type TPS with scientific approach more effective than the cooperative learning model type STAD cooperative with the scientific approach in terms of mathematical communication skills.Keywords : effectivity, cooperative learning model type Think Pair Share (TPS), cooperative learning model type Student Teams-Achievement Division (STAD), scientific approach, mathematical communication skill.